The effect of group-based exercise on cognitive performance and mood in seniors residing in intermediate care and self-care retirement facilities: a randomised controlled trial. Issue 8 (16th October 2008) - Brown, A K; Liu-Ambrose, T; Tate, R; Lord, S R
Abstract : Objective: To determine the effect of a general group-based exercise programme on cognitive performance and mood among seniors without dementia living in retirement villages. Design: Randomised controlled trial. Setting: Four intermediate care and four self-care retirement village sites in Sydney, Australia. Participants: 154 seniors (19 men, 135 women; age range 62 to 95 years), who were residents of intermediate care and self-care retirement facilities. Intervention: Participants were randomised to one of three experimental groups: (1) a general group-based exercise (GE) programme composed of resistance training and balance training exercises; (2) a flexibility exercise and relaxation technique (FR) programme; or (3) no-exercise control (NEC). The intervention groups (GE and FR) participated in 1-hour exercise classes twice a week for a total period of 6 months. Main outcome measures: Using standard neuropsychological tests, we assessed cognitive performance at baseline and at 6-month re-test in three domains: (1) fluid intelligence; (2) visual, verbal and working memory; and (3) executive functioning. We also assessed mood using the Geriatric Depression Scale (GDS) and the Positive and Negative Affect Schedule (PANAS). Results: The GE programme significantly improved cognitive performance of fluid intelligence compared with FR or NEC. There were also significant improvements in the positive PANAS scale within both the GE and FR groups and an indication that the two exercise programmes reduced depression in those with initially high GDS scores. Conclusions: Our GE programme significantly improved cognitive performance of fluid intelligence in seniors residing in retirement villages compared with our FR programme and the NEC group. Furthermore, both group-based exercise programmes were beneficial for certain aspects of mood within the 6-month intervention period.